Evaluating patients presenting to the emergency department after syncope: validation of the Canadian Syncope Risk Score. Issue 11 (7th May 2019) - Chan, Jason; Hunter, Jonathan; Morel, Douglas; Ballard, Emma; Brain, David; Yan, Alan; Hocking, Julia
Abstract: Background: Syncope is a common problem but can have any of a broad range of underlying causes. Initial evaluation of the patient in the emergency department often does not identify a specific cause, and the cornerstone of management is reliable risk stratification with clinical decision rules. Objectives: The primary objective is to validate the utility and safety of the Canadian Syncope Risk Score (CSRS) as a clinical decision rule when assessing patients who present with syncope to Australian emergency departments. Our secondary objective is to evaluate the economic benefits of diverting patients with syncope at low risk of serious adverse events from admission to hospital. Methods and analysis: Prospective, observational study. Patients aged 18 years or more who present to the emergency department (ED) after syncope in the preceding 24 hours and have returned to their baseline state will be enrolled. Patients will be contacted by telephone to determine whether they have experienced any adverse events within 30 days of their initial presentation to the ED. The CSRS will be applied retrospectively to determine the relationship between whether patients were admitted to hospital or discharged home and the reporting of serious adverse events for each CSRS risk level. We will also undertake a cost‐effectiveness analysis from the health care perspective. Ethics approval: Prince Charles Hospital Human Research Ethics Committee (reference, HREC/17/QPCH/48). Dissemination of results: Outcomes will be disseminated by Queensland Health and the funding body via social media, presented at local and national emergency medicine conferences, and published in international emergency medicine and health economics journals. Clinical trials registration: Not applicable.